1 answer

(click or scroll down)

## To solve for (the square root of 7 - the square root of 3) squared, you can follow these steps:

1. Start with the expression (sqrt(7) - sqrt(3))^2.

2. Apply the rule of expanding a binomial squared, which states that (a - b)^2 = a^2 - 2ab + b^2.

3. In this case, let a = sqrt(7) and b = sqrt(3). Substituting these values into the formula, we get (sqrt(7))^2 - 2(sqrt(7))(sqrt(3)) + (sqrt(3))^2.

4. Simplify each term: sqrt(7)^2 = 7, sqrt(3)^2 = 3.

5. Multiply the middle term: 2(sqrt(7))(sqrt(3)) = 2sqrt(21).

6. Combine the simplified terms: 7 - 2sqrt(21) + 3.

7. Simplify further: 10 - 2sqrt(21).

Therefore, (the square root of 7 - the square root of 3)^2 equals 10 - 2sqrt(21).